Geraniin exerts cytoprotective effect against cellular oxidative stress by upregulation of Nrf2-mediated antioxidant enzyme expression via PI3K/AKT and ERK1/2 pathway - Wang, Peng; Peng, Xiao; Wei, Zuo-Fu; Wei, Fu-Yao; Wang, Wei; Ma, Wei-Dong; Yao, Li-Ping; Fu, Yu-Jie; Zu, Yuan-Gang (Biochimica et biophysica acta, 2015)
Geraniin, an active compound with remarkable antioxidant activity, was isolated from Geranium sibiricum. The present study aimed to investigate whether geraniin has the ability to activate Nrf2, induce antioxidant enzyme expression and protect cells from oxidative damage. The cells were pretreated with geraniin for 24h and exposed to hydrogen peroxide (H2O2) for 4h. Intracellular reactive oxygen species (ROS) levels, mitochondrial membrane potential and apoptosis were measured. We also investigated intracellular glutathione (GSH) levels and changes in nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated signaling cascade in cells treated with geraniin. We investigated the protective effects of geraniin against H2O2-induced apoptosis in HepG2 cells. Geraniin significantly reduced H2O2-induced oxidative damage in a dose dependent manner. Further, geraniin induced the expression of heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase-1 (NQO1) and level of glutathione (GSH) in a concentration- and time-dependent manner, and increased Nrf2 nuclear translocation. The Nrf2-related cytoprotective effects of geraniin were PI3K/AKT and extracellular signal-regulated protein kinase1/2 (ERK1/2) pathway-dependent. However, inhibitors of PI3K/AKT and ERK1/2 (LY294002 or U0126) not only suppressed geraniin-induced nuclear translocation of Nrf2 but also abolished the expression of HO-1, NQO1 and GSH. These results demonstrated that geraniin induced Nrf2-mediated expression of antioxidant enzymes HO-1 and NQO1, presumably via PI3K/AKT and ERK1/2 signaling pathways, thereby protecting cells from H2O2-induced oxidative cell death. Geraniin, at least in part, offers an antioxidant defense capacity to protect cells from the oxidative stress-related diseases. [Display omitted] •Geraniin suppressed H2O2-induced cytotoxicity in HepG2 cells.•Geraniin induced the expression of antioxidant genes and intracellular GSH level.•Geraniin induced the nuclear translocation of Nrf2.•Geraniin activates PI3K/AKT and ERK 1/2 signaling pathways.